Wound Care for Post Partum Patient with Wound Dehiscence: Case Study - Agustian, M. Fery; Budiarti, K. Dewi (Nursing Case Insight Journal, 2023)
Wound dehiscence is a significant risk following a caesarean section, with approximately 14% of cases occurring post-surgery. At Dr. Slamet Garut Hospital in West Java Province, the incidence of wound dehiscence after caesarean section was 1.35% in 2019, and this number has been increasing annually. In 2019, there were 4 patients with wound dehiscence in the Lower Kalimaya room and 6 patients in the Jade room. A case study was conducted to evaluate the effectiveness of treating wound dehiscence using 0.9% NaCl, and the results indicated that this treatment could expedite the healing process. This study focused on patients with delayed post-surgical recovery and demonstrated that wound treatment using 0.9% NaCl can be beneficial for patients with specific wound dehiscence characteristics.